Sarcoidosis with cutaneous perineural granulomas and neurological manifestations: A potential mimicker of leprosy. (13th February 2020) - Kazi, Rashek; Kazlouskaya, Viktoryia; Ho, Jonhan; Karunamurthy, Arivarasan
Abstract: Sarcoidosis is a granulomatous condition with diverse clinical presentations, including neurological findings. It was previously hypothesized that perineural sarcoidal granulomas in the skin may be an explanation of small‐fiber neuropathy. Herein, we present a case of a 55 year old female with anesthetic cutaneous lesions mimicking leprosy clinically and histopathologically and discuss the importance of this differential diagnosis.